East Asia: Tradition and transformation - John K Fairbank (Houghton Mifflin, 1989)
The book presents the history of East Asia. The peoples of China, Japan, Korea, and VietNam have experiented great disasters of warfare and invasion and have achieved great feats of national survival and regeneration. Japan has adjusted to its new position as an economic superpower; the vast problems faced by the Chinese people in the last decade have become better understood; Korea remains a divided country; and the people of VietNam are still recuperating from the devastation of war. But clearly each of these four countries has now entered a new age. Their peoples may well feel that the past has been but the prologue to a hopeful future. China has repudiated the policies of Mao and struck out in new directions hoping to initiate sustained economic growth. South Korea, Taiwan, Hongkong, and Singapore have begun modern economic growth and have moved establish more open societies. North Korea and VietNam, like China, have begun to change their policies in order not to fall farther behind. Japan, economically larger than all the rest of non-Soviet Asia put together, has begun to adjust to having caught up with the West. Its prowess in manufacturing has been matched by its advances in scientific technology, and its has begun to make itas influence felt in world financial markets